Distributing complementary resources across multiple periods with stochastic demand - CHENG, Shih-Fen (Institutional Knowledge at Singapore Management University, 2008)
In this paper, we evaluate whether the robustness of a market mechanism that allocates complementary resources could be improved through the aggregation of time periods in which resources are consumed. In particular, we study a multi-round combinatorial auction that is built on a general equilibrium framework. We adopt the general equilibrium framework and the particular combinatorial auction design from the literature, and we investigate the benefits and the limitation of time-period aggregation when demand-side uncertainties are introduced. By using simulation experiments, we show that under stochastic conditions the performance variation of the process decreases as the time frame length (time frames are obtained by aggregating time periods) increases. This is achieved without causing deterioration in the mean performance.